Immunogenicity of the Oral Rabies Vaccine Strain SPBN GASGAS in Dogs Under Field Settings in Namibia - Molini, Umberto; Hassel, Rainer; Ortmann, Steffen; Vos, Ad; Loschke, Malaika; Shilongo, Albertina; Freuling, Conrad M.; Müller, Thomas (Frontiers in Veterinary Science, 2021)
Dog-mediated rabies is endemic throughout Africa. While free-roaming dogs that play a crucial role in rabies transmission are often inaccessible for parenteral vaccination during mass dog vaccination campaigns, oral rabies vaccination (ORV) is considered to be a promising alternative to increase vaccination coverage in the these hard-to-reach dogs. The acceptance of ORV as an efficient supplementary tool is still low, not least because of limited immunogenicity and field trial data in local dogs. In this study, the immunogenicity of the highly attenuated 3rd generation oral rabies vaccine strain SPBN GASGAS in local free-roaming dogs from Namibia was assessed by determining the immune response in terms of seroconversion for up to 56 days post vaccination. At two study sites, free-roaming dogs were vaccinated by administering the vaccine either by direct oral administration or via a vaccine loaded egg bait. Pre and post vaccination blood samples were tested for rabies virus neutralizing as well as binding antibodies using standard serological assays. A Multiple Logistic Regression analysis (MLR) was performed to determine a possible influence of study area, vaccination method, and vaccine dose on the seroconversion obtained. About 78% of the dogs vaccinated by the oral route seroconverted (ELISA), though the seroconversion as determined by RFFIT was slightly lower. None of the factors examined had a significant effect on seroconversion rate. This study confirms the immunogenicity of the vaccine strain and the potential utility of ORV for the control of dog-mediated rabies in African dogs.